2017
DOI: 10.1080/11250003.2016.1273974
|View full text |Cite
|
Sign up to set email alerts
|

Chironomidae larvae in hypersaline waters of the Crimea: diversity, distribution, abundance and production

Abstract: Chironomidae larvae may represent more than 70% of total Arthropoda numbers in hypersaline waters. Crimea, the largest peninsula of the Black Sea, has more than 50 hypersaline water bodies of marine and continental origin. Chironomidae larvae are common components of their ecosystems, but they still are poorly understood. This paper summarizes the results of a long-term study (2007-2016) of chironomids in Crimean hypersaline waters. More than 400 samples from 38 water bodies were used for analysis. The maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 41 publications
(39 reference statements)
0
31
0
8
Order By: Relevance
“…In plankton, chironomid larvae had become a constant component. Abundance of chironomid larvae sharply increased in the bottom community (Shadrin et al, ; Soloveva et al, ), and B. noctivagus , the most halotolerant species among Chironomidae worldwide, is the dominant species in the bay now (Shadrin, Anufriieva, Belyakov, & Bazhora, ). It was previously shown that at high salinity, a significant number of the chironomid larvae transit from life on the bottom to existence in plankton and/or in floating mats of the green filamentous alga Cladophora (Shadrin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In plankton, chironomid larvae had become a constant component. Abundance of chironomid larvae sharply increased in the bottom community (Shadrin et al, ; Soloveva et al, ), and B. noctivagus , the most halotolerant species among Chironomidae worldwide, is the dominant species in the bay now (Shadrin, Anufriieva, Belyakov, & Bazhora, ). It was previously shown that at high salinity, a significant number of the chironomid larvae transit from life on the bottom to existence in plankton and/or in floating mats of the green filamentous alga Cladophora (Shadrin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Among Diptera, the permanent inhabitants of the B. Samoroda River were Chironomidae, Ceratopogonidae, Ephydridae and Psychodidae. Species of these families are widespread in saline waters of the world (Armitage et al 1994;Velasco et al 2006;Przhiboro 2014;Shadrin et al 2017). Chironomid larvae were found in rivers with salinity up to 115 g l -1 (Rutherford and Kefford 2005), Ceratopogonid larvae can tolerate salinity up to 108 g l -1 (Rutherford and Kefford 2005) and Ephydridae larvae up to 100 g l -1 (Velasco et al 2006).…”
Section: Faunamentioning
confidence: 99%
“…Не менее 38 их видов разных подсемейств могут существовать при солёности более 35 г/л, 16 из них обитают и при солёности более 100 г/л (Shadrin et al, 2017). При этом при 150 г/л и выше отмечено присутствие лишь 3 видов.…”
Section: результатыunclassified
“…Осмоадаптация у них осуществляется на клеточном уров-не путем синтеза или/и получения извне и накопления в клетках совместимых ос-молитов -низкомолекулярных органических соединений. Среди Diptera, включая хирономид, есть виды, использующие одну из этих стратегий или сразу оба меха-низма (Patrick, Bradley, 2000;Renault et al, 2016;Shadrin et al, 2017). Механизмы осморегуляции, как и синтез осмолитов, требуют больших затрат энергии, поэтому получение осмолитов из внешней среды может существенно снижать затраты энергии на процессы осмоадаптации.…”
Section: результатыunclassified
See 1 more Smart Citation